Effect of Varying Rates and Methods of Carrier based and Liquid Azotobacter and PSB Biofertilizers on Yield and Nutrient Uptake by Wheat (Triticum aestivum L.) and Soil Properties - Navneet Pareek; K.P. Raverkar, R.N. Khandare, Ramesh Chandra (Journal of the Indian Society of Soil Science, 2016)
A field experiment was conducted during 2012-13 and 2013-14 in Mollisol at Pantnagar to examine the effects of varying rates and methods of application of carrier based and liquid Azotobacter and PSB biofertilizers in combination with chemical fertilizers in wheat (Triticum aestivum L.). Application of 100% NP showed maximum plant height, grain and straw yields, nutrient uptake and available NPK in soil after harvesting. Soil application of carrier biofertilizer at 10 kg ha-1 and liquid biofertilizer at 0.625 and 1.25 L ha-1 in combination with 75% NP gave significantly more plant height over 75% NP alone at different intervals. These treatments were at par with 100% NP alone in plant height and grain and straw yields. The mean grain yield due to soil application of carrier biofertilizer at 10 kg ha-1 and liquid biofertilizers at 0.625 and 1.25 L ha-1 with 75% NP was significantly more by 10.9, 10.5 and 10.8 per cent over 75% NP alone, respectively. The respective increases in mean straw yield due to these treatments were 8.6, 8.2 and 9.1 per cent, respectively over 75% NP alone. The trend that observed in grain and straw yield was also observed in various yield attributes viz., total tillers, effective tillers, ear length, and number of spikelet/ear, number of grains/ear and 1000 grain weight. These treatments also significantly increased N, P and K uptake by grain and straw. All biofertilizer treatments with 75% or 50% NP gave significantly more available NPK in soil after harvesting over respective doses of NP alone. The different biofertilizer treatments with 50% NP also showed similar positive response for growth, yields, nutrient uptake and available NPK in soil in comparison to 50% NP alone. The carrier and liquid formulations of the biofertilzers at respective rates were comparable in their performance. Irrespective of formulation and doses, application of biofertilizers in soil was found better than seed treatment for different recorded parameters. The increasing rates of the carrier and liquid biofertilizers applied in soil slightly improved the various recorded parameters. An application of 0.625 L ha-1 liquid biofertilizers in soil with 75% NP was found optimum for the growth, yield, nutrient uptake and available NPK in soil after harvesting.